2021
DOI: 10.1016/j.jbc.2021.101170
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization explains loss of dNTPase activity of the cancer-specific R366C/H mutant SAMHD1 proteins

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(154 reference statements)
1
7
0
Order By: Relevance
“…While the SAMHD1 protein was detected at 72 kDa by immunoblotting in normal 48BR cells, this band was not detectable in the patient's CS213NG cells (Figure 2B). This result is consistent with previous reports describing the instability nature of the missense variant, p. Y155C, in vitro (34), or in leukemia patients' cells with this mutation (33).…”
Section: Exome Sequencing Identifies Loss Of Function Variants In Samhd1supporting
confidence: 93%
“…While the SAMHD1 protein was detected at 72 kDa by immunoblotting in normal 48BR cells, this band was not detectable in the patient's CS213NG cells (Figure 2B). This result is consistent with previous reports describing the instability nature of the missense variant, p. Y155C, in vitro (34), or in leukemia patients' cells with this mutation (33).…”
Section: Exome Sequencing Identifies Loss Of Function Variants In Samhd1supporting
confidence: 93%
“…In addition, we did not find a significant correlation between mutations and SAMHD1 expression in MCL and between mutations and clinical outcome. Although the newly found mutations had no obvious effect on the prognosis of MCL patients, some SAMHD1 mutations previously reported were associated with chronic lymphocytic (B-cell) leukemia development (11) and changed its dNTPase activity (39). It will be very interesting to study the impact of these four new mutations we found in this study on the structure and function of the SAMHD1 molecule.…”
Section: Discussionmentioning
confidence: 60%
“…dNTP hydrolase, nuclease recruitment, innate immunity suppression, nucleic acid binding), it is difficult to hypothesise the outcome for cancer biology, given the impact of the loss of SAMHD1 can be hypothesised to have different outcomes depending upon the biological role in question. This approach was applied in a recent study characterising the colon cancer and leukaemia‐associated R366C/H mutant, and showed that while this mutation retains noncatalytic roles of SAMHD1, the dNTPase activity is abolished [ 130 ]. Accordingly, this mutation could contribute to elevated dNTP pools, which are commonly reported in cancer cells [ 131 ].…”
Section: Samhd1mentioning
confidence: 99%